Investigation on fracture process of concrete - Sonali Bhowmik; Sandeep Dubey; Sonalisa Ray (Fracture and Structural Integrity)
A series of geometrically similar concrete beams of small, medium and large beam sizes has been tested under the action of monotonic and fatigue loading. Digital image correlation technique has been utilized to understand the fracture processes and crack growth behavior in concrete. The tip of effective crack in concrete beams under static and fatigue loading has been calculated through DIC analysis. Further, existence of size effect has been observed when the results of geometrically similar concrete beams were compared.